2021
DOI: 10.3892/mmr.2021.12375
|View full text |Cite
|
Sign up to set email alerts
|

hsa‑miR‑15a‑5p inhibits colon cell carcinoma via targeting CCND1

Abstract: Colon carcinoma is one of the most common cancers worldwide. Epidemiological studies have revealed that colon cancer is the third leading cause of cancer-related deaths, which is due to the increased incidence and mortality rates. However, the treatment strategies for colon cancer remain unsatisfactory for patients, especially for those with advanced or recurrent colon cancer. Dysregulated microRNAs (miRNAs) are considered to influence tumor development and metastasis. However, the molecular mechanism through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Higher expression of hsa-miR-15b-5p has been reported to be associated with a short survival time of patients with LGG (36). Has-miR-15a-5p promotes the proliferation and invasion of colorectal cancer by targeting CCND1 (37). Hsa-mir-16-5p is downregulated in giant cell tumors (38).…”
Section: Discussionmentioning
confidence: 99%
“…Higher expression of hsa-miR-15b-5p has been reported to be associated with a short survival time of patients with LGG (36). Has-miR-15a-5p promotes the proliferation and invasion of colorectal cancer by targeting CCND1 (37). Hsa-mir-16-5p is downregulated in giant cell tumors (38).…”
Section: Discussionmentioning
confidence: 99%
“…However, we could see that overexpression of hsa‐miR‐122b might result in reduced cell viability, plausibly due to increased apoptosis. Previous studies have linked hsa‐miR‐15a‐5p to sporadic endometrial cancer 46 and colorectal cancer, 47 both being hallmark cancers of LS. In our analysis, hsa‐miR‐15a‐5p was seen to target several genes, including known oncogenes and tumor suppressor genes such as CCND1 , CDK6 and DICER1 , thus suggesting biomarker potential also in LS.…”
Section: Discussionmentioning
confidence: 99%
“…It is supposed that hsa-miR-15a-5p is involved in crucial biological processes through its targeted gene, G1/S-specific cyclin-D1 (CCND1). Bioinformatics and dual-luciferase reporter assay analyses predicted CCND1 as a target of hsa-miR-15a-5p [ 64 ]. Additionally, a recent study revealed that miR-15a-5p promotes apoptosis and inhibits cell growth through the changes in expression levels of pro-survival genes and proteins, including Bcl-xl and Bcl-2 and inhibition of oncogenic transcription factors such as CCND2, Bcl-6, MYC, and PIK3R1 [ 65 ].…”
Section: Discussionmentioning
confidence: 99%